Client perceptions of independent living annuity advice - Moroeroe, Albert (University of the Free State, 2014)
Most working South Africans retire with only their retirement savings to draw an income from. Choosing the appropriate investment vehicle to provide an income is critical, considering that only 6% of South Africans retire independently. A living annuity is a good investment vehicle for retirement income, but is a complex product and retirees should seek advice from a financial planner before investing their retirement savings in this investment vehicle. This study focuses on perceptions of affluent clients about the advice that they receive concerning their living annuities. The client participants are living annuity clients of a wealth management firm in central South Africa. National Treasury is of the view that living annuities are complex and expensive and is seeking to reform the living annuity industry in an attempt to secure better outcomes for retirees. The proposed reforms will, amongst other things, affect the fees that financial planners can earn for giving advice on living annuities, which will potentially impact the revenue streams of financial planners and the wealth management firms that they represent. It is, therefore, important to determine whether the advice retirees receive is adding value to their financial well-being and whether the advice fees charged are justified. A major objective of the study is, therefore, to assess whether clients are satisfied with the advice they receive as well as whether they are satisfied paying for the advice. This is important for financial planners and wealth management firms to understand in order service the needs of their clients. It is also important, because it will enable wealth management firms to employ the most appropriate strategies to grow their businesses sustainably and improve profitability. The study combines a literature review, a client perception survey and a financial planner survey. The results of the two surveys are compared and analysed and findings are discussed. Recommendations are then based on the findings as well as the literature review. The study shows that the financial planners of the firm are adding value to the financial well-being of their clients and that the majority of the clients were satisfied with the advice that they received, but that less than half of the clients were satisfied paying for advice. The advice given should be continuously adding value that can be understood by clients. The findings of the study also show that customer relationship management should be the tool used to improve clients’ levels of satisfaction and that it has the potential to improve client loyalty and profitability.
Dissertation (MBA (Business Administration))--University of the Free State, 2014
Keywords: Living annuity; Retirement savings; Financial planning; Wealth management; Client satisfaction